Extraction of Capsaicin from Black and White Pepper - B.S, Naveen Prasad; Sivamani S, (Journal of Sustainable Materials Processing and Management, 2022)
Capsaicin has general impressive health benefits such as anticancer, stimulates digestion and enables weight loss. The aim of this study is to extract capsaicin from black pepper and white pepper by using polar (Ethanol) and nonpolar (Acetone) solvents and to maximize the percentage yield of capsaicin. The effect of temperature and solid to solvent ratio on percentage yield is investigated for extraction of capsaicin from black pepper and white pepper. The percentage yield of capsaicin is higher for acetone than ethanol for both black and white pepper at the temperature and solid to solvent ratio of 50 oC and 1:10, respectively. Also, the percentage yield of capsaicin is higher for ethanol than acetone for both black and white pepper at the temperature and solid to solvent ratio of 70 oC and 1:10, respectively. Hence, black and white pepper could be the potential substrates for the extraction of capsaicin.